UMPSA implements SSPA Option provision - Siti Sakinah, Mohtar (UMPSA, 2024)
PEKAN, 21 October 2024 – The Human Resources Management Division (BPSM) under the Registrar’s Department, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), has conducted a session to distribute the Public Service Remuneration System (SSPA) option forms to all its employees.